Pengaruh durasi penyimpanan asi perah di thermoelectric cooler terhadap kualitas ASI - Istikomah; Heda Melinda Nataprawira; Dzulfikar DLH (MEDIA ILMU KESEHATAN, 2021)
Background: Breastmilk is a very important need during the growth and development of neonates including nutrition and improve the health. An effort is needed to solve the problem of how working mothers could still breastfeed their babies exclusively. In Indonesia, the working mothers leave their babies averagely for 7–10 hours daily to work or other purpose. The facility to keep the breastmilk in good condition is not always available in every public place, while breastmilk storage in room temperature only survive for 3–4 hours. Therefore, a simple tool that generates cold temperature was designed to replace refrigerator.Objective: To find out the ability of thermoelectric cooler in maintaining the quality of breast milk up to 8 hours.Methods: This is an analytic study using laboratory experimental approach. We analyzed 88 breastmilk samples obtained from 22 breastfeeding mothers in Taman Sari district Bandung. Each breast milk sample was divided into 4 sections to be tested at 0, 4, 8, and 12 hours.Result: All of breast milk samples were safe from the Mesofil aerob, Enterobactericeae, and pathogen bacteria. But, about 52(51.9%) of the samples were contaminated by fungi since 0 hour. Statistical analysis showed no significant difference in breast milk storage in thermoelectric cooler until 8 hours with ρ value=1.000.Conclusion: Thermoelectric cooler maintains breast milk quality in storage duration up to 8 hours.